Juridical Analysis of Doctors Engaging in Collusion with Pharmaceutical Companies in Prescription of Medications - Heriman, Amanda Regina Pallas; Caroline; Hasian, Clarisa Permata; Tobing, Ega Yolanda Lumban; Alexander, Johan; Naibaho , Novia (Lex Prospicit, 2024)
In Indonesia, the legal rules that regulate the prohibition of doctors receiving gifts from pharmaceutical companies have not had a significant impact because the existing regulations only exist in the realm of ethics and administration. As a result, the collaboration between doctors and pharmaceutical companies in prescribing drugs continues and has a negative impact on patients. This research analyses the actions of doctors and pharmaceutical companies colluding in prescribing drugs to patients. The purpose of this research is to understand the legal responsibility of doctors and pharmaceutical companies colluding in prescribing drugs to patients, and also to understand the comparison of prevention of collusion between doctors and pharmaceutical companies in drug marketing in Indonesia and the United States. This study uses normative legal research because this research is only intended for written regulations, so this research is closely related to literature because it requires secondary data. The findings of this study indicate that collusion between doctors and pharmaceutical companies, which involves unethical or illegal agreements, can result in civil legal liability. However, if we review the law in the United States, the United States has stronger regulations, better transparency, and stricter legal sanctions in preventing collusion between doctors and pharmaceutical companies in drug marketing compared to Indonesia.